2016
DOI: 10.2131/jts.41.813
|View full text |Cite
|
Sign up to set email alerts
|

A new designer drug 5F-ADB activates midbrain dopaminergic neurons but not serotonergic neurons

Abstract: -N-[[1-(5-fluoropentyl)-1H-indazol-3-yl]carbonyl]-3-methyl-D-valine methyl ester (5F-ADB) is one of the most potent synthetic cannabinoids and elicits severe psychotic symptoms in humans, sometimes causing death. To investigate the neuronal mechanisms underlying its toxicity, we examined the effects of 5F-ADB on midbrain dopaminergic and serotonergic systems, which modulate various basic brain functions such as those in reward-related behavior. 5F-ADB-induced changes in spontaneous firing activity of dopaminer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Little is known about non-cannabinoid receptor-mediated effects on the human body. There is indication that at least some of the first-generation synthetic cannabinoids act at receptors other than cannabinoid CB 1 and CB 2 (Wiley et al, 2016), and a compound from the present study, 5F-MDMB-PINACA, was found to activate midbrain dopamine neurons, but not serotonin neurons (Asaoka et al, 2016). These findings imply that at least some of the adverse effects targeting non-CNS organ systems such as heart, liver and kidney may be mediated through non-cannabinoid mechanisms, although the bradycardia induced by 5F-AMB and MDMB-FUBINACA was reversed by a CB1 antagonist (Banister et al, 2016).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Little is known about non-cannabinoid receptor-mediated effects on the human body. There is indication that at least some of the first-generation synthetic cannabinoids act at receptors other than cannabinoid CB 1 and CB 2 (Wiley et al, 2016), and a compound from the present study, 5F-MDMB-PINACA, was found to activate midbrain dopamine neurons, but not serotonin neurons (Asaoka et al, 2016). These findings imply that at least some of the adverse effects targeting non-CNS organ systems such as heart, liver and kidney may be mediated through non-cannabinoid mechanisms, although the bradycardia induced by 5F-AMB and MDMB-FUBINACA was reversed by a CB1 antagonist (Banister et al, 2016).…”
Section: Discussionmentioning
confidence: 54%
“…The compounds tested in the present study (MDMB-PINACA, MDMB-CHMICA, MDMB-FUBINACA, ADB-FUBINACA, and AMB-FUBINACA) all act as agonists at CB1 receptors (Banister et al, 2015, 2016; Gamage et al, 2018). In addition, 5F-MDMB-PINACA activates midbrain dopamine neurons, but has no effect on serotonin neurons (Asaoka et al, 2016). In confirmation that at least some of the behavioral effects of these compounds are mediated by CB1 receptors, the bradycardia and hypothermia induced by 5F-AMB and MDMB-FUBINACA was reversed by a CB1 antagonist (Banister et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As these symptoms resemble the serotonin syndrome, the author and colleagues investigated the effect of 5F-ADB on midbrain serotonergic neurons. However, 5F-ADB did not affect serotonergic activity; rather, dopaminergic firings were readily increased [19]. Therefore, the neuronal mechanism underlying catalepsy seen in SC abuser is unclear.…”
Section: Lineage and Timeline Of Scmentioning
confidence: 99%
“…It is known to inhibit the growth of fibroblasts in primary neuronal cell cultures [ 166 , 167 ]. In recent years, there has been some interest in N-[[1-(5-fluoropentyl)-1H-indazol-3-yl]carbonyl]-3-methyl-D-valine methyl ester (5F-ADB), a novel cannabinoid which uses D-valine methyl ester as a scaffold [ 81 ]. This drug can elicit severe psychotic symptoms in humans, sometimes causing death.…”
Section: Inactive D-amino Acids With Interesting Derivatives or Otmentioning
confidence: 99%
“…This drug can elicit severe psychotic symptoms in humans, sometimes causing death. It was found that 5F-ADB activated brain dopaminergic neurons through activation of cannabinoid 1-receptor [ 81 ]. Interestingly, the L-valine form of this drug while still toxic, appears to require a higher dosage before fatality occurs [ 168 , 169 , 170 ].…”
Section: Inactive D-amino Acids With Interesting Derivatives or Otmentioning
confidence: 99%